An investigation of the determinants of international short-term capital movements with special reference to the position of South Africa (1973-1983) - Smit, Benjamin Willem (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Comm.) -- University of Stellenbosch, 1984.